2021
DOI: 10.1242/dev.194670
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 regulates a temporal transcriptional program to promote progression of cortical neural progenitors

Abstract: Radial glia (RG) in the neocortex sequentially generate distinct subtypes of projection neurons, accounting for the diversity and complex assembly of cortical neural circuits. Mechanisms that drive the rapid and precise temporal progression of RG are beginning to be elucidated. Here we reveal that the RG-specific transcriptional regulator PRDM16 promotes the transition of early to late phase of neurogenesis in the mouse neocortex. Loss of Prdm16 delays the timely progression of RG, leading to defective cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 71 publications
(129 reference statements)
2
15
0
Order By: Relevance
“…1A ). Previously we reported that animals of the Prdm16 knockout (KO) null allele, Prdm16 cGT ( cGT ), show severely reduced ChP structure ( Fig 1B ) (Bjork et al, 2010; He et al, 2021; Strassman et al, 2017). In the Prdm16 KO mutant, expression of the ChP marker gene, Ttr , is not only reduced in the lateral ventricle (tChPs) but also in the fourth ventricle (hChP) ( Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…1A ). Previously we reported that animals of the Prdm16 knockout (KO) null allele, Prdm16 cGT ( cGT ), show severely reduced ChP structure ( Fig 1B ) (Bjork et al, 2010; He et al, 2021; Strassman et al, 2017). In the Prdm16 KO mutant, expression of the ChP marker gene, Ttr , is not only reduced in the lateral ventricle (tChPs) but also in the fourth ventricle (hChP) ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The PRDM16 protein is highly expressed in the nucleus of NSCs in embryonic brain tissues ( Fig. 1B , and (He et al, 2021)). Unexpectedly, the protein becomes nearly undetectable when primary NSCs are cultured in vitro ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Loss of Prdm16. which regulates genes that are dynamically expressed between early and late neurogenesis, results in the extended production of deep layer neurons into periods when progenitors would usually be producing more superficial Brain Behav Evol 2022;97:8-32 DOI: 10.1159/000521678 neurons [He et al, 2021]. A recent article reported that opposing gradients of microRNAs (miR-9, miR-128 and Let-7) are expressed in progenitors throughout development, and that transient alterations of their expression can shift neuron production from early-to-later born fates and vice versa [Shu et al, 2019].…”
Section: The Timing and Sequence Of Successive Birth Of Different Ide...mentioning
confidence: 99%